El Excentrico, 1973-02-05 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
February 5, 1973 [5 de febrero de 1973]. No volume or issue number. Cover has a photograph for the 26th Annual Food Drive Benefit Dances at the Starlight Ballroom in San Jose.